IMPLEMENTASI APLIKASI PEMBELAJARAN UNTUK ANAK BERBASIS ANDROID - Sam'ani, Sam'ani; Sutami, Sutami; Qamaruzzaman, Muhammad Haris (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2019)
Permendiknas No. 16/2007 concerning Academic Qualification Standards and Teacher Competence, Pedagogical Competence of 5th / Senior High School teachers says that "High School / Vocational Teachers must utilize information and communication technology for the benefit of learning". Reinforced in Permendiknas No. 41 of 2007 concerning Process Standards, in accordance with Graduates Competency Standards and Content Standards, the learning principle used in point 13 states that "Utilization of information and communication technology to improve the efficiency and effectiveness of learning". But now when the world is entering the era of the industrial revolution 4.0. or the fourth world industrial revolution where technology has become the basis in human life the use of information and communication technology for learning must begin at the Early Childhood Education level (PAUD) in order to be more interesting and interactive and increase children's interest and curiosity in what is taught . The method of applying science and technology used is mobile technology which is very popular at the moment, namely the Android-based children's learning application as an effort to increase knowledge and understanding as well as increase the learning interest of students in grades 2, 3 and 4 of Bereng Kajang Elementary School I. The purpose of this program is to increase knowledge and understanding and increase learning interest of students in grades 2, 3 and 4 of Bereng Kajang I Elementary School on various things including letters, numbers, colors, vegetables, animals, fruits, jobs and vehicles. Both in Indonesian and English pronunciation through the implementation / dissemination of learning applications for children based on Android. Keywords: Learning applications, Children, Android, Implementation